Assessing campus diversity initiatives a guide for campus practitioners - Garcia, Mildred; Nettles, Michael T.; Sedlacek, William E.; Smith, Daryl G. (Washington Association of American Colleges and Universities, 2001)
This volume, one in a series of three monographs, is a guidebook to evaluating campus diversity initiatives. Chapter 1 introduces campus diversity initiatives. Chapter 2, "Evaluation and Diversity," explores the need for assessment of such initiatives. Chapter 3, "Designing a Campus Diversity Evaluation," presents general concepts and guidelines and identifies various foci of diversity assessment. It also raises questions evaluators should consider as they plan assessments and discusses data collection and analysis. Chapter 4, "Frameworks for Evaluation," offers some larger frameworks for evaluation and discusses performance indicators linked to campus diversity work. Seven appendixes contain instruments for use in evaluating campus diversity programs and student experiences. (Contains 24 references.) (SLD).
Introduction-- Diversity defined-- Using this handbook-- Evaluation and diversity-- Why evaluate?-- Dimensions and states-- Designing a campus diversity evaluation-- Define the purpose-- Determine the audience-- Assemble the evaluation team-- Identify the context-- Target the topic-- Formulate the questions-- Obtain the data-- Assess the data-- Analyze the data-- Report the findings-- Frameworks for evaluation-- Institutional audit-- Models and theories-- A final note
"This monograph is the third in a series of the three publications that are part of AAC&U's project."
Keywords: College students -- United States -- Attitudes